Intertemporal Distortions in the Second Best - Albanesi, S.; Armenter, R. (Review of Economic Studies, 2012)
This paper studies the long-run properties of intertemporal distortions in a broad class of second-best economies. Our unified framework encompasses and extends many well-known models, such as variants of the Ramsey taxation model with aggregate or idiosyncratic risk, and economies with incentive compatibility constraints due to limited commitment, political economy, self-enforcement or private information, or combinations of these. We identify a sufficient condition that rules out permanent intertemporal distortions: if there exists an allocation that satisfies all constraints and eventually converges to the limiting first-best allocation, then intertemporal distortions are temporary in the second best. This result uncovers a common optimality principle linking the intertemporal allocation of resources with the ability to front-load distortions for this broad class of environments. A series of applications illustrates the significance of these findings.